Protection of lands in Ukraine: scientific and management solutions in the conditions of military actions - Tretiak, A.; Tretiak, V.; Priadka, T.; Kapinos, N.; Hunko, L.; Tretiak, R.; Tretiak, N. (Land Management, Cadastre and Land Monitoring, 2024)
The research by the authors reveals that after the legislative definition of land protection content in Ukraine, neither scientific nor managerial support for the implementation of the defined tasks has been organized. To date, land protection standards have not been developed, and neither land planning nor economic instruments are being implemented. Furthermore, the situation concerning land protection has deteriorated due to ongoing military actions on Ukraine’s territory. During research, the authors calculated the amount of damage from soil pollution according to the Methodology proposed by the Ministry of Environmental Protection and Natural Resources of Ukraine dated 04.04.2022 No. 167. According to the calculations, the amount of damage to 1 hectare of arable land contaminated with petroleum products will be 506 thousand UAH/ha, while the norm for the Kyiv region as of December 18, 2023 is 2,362 thousand UAH/ha, which is 4.66 times higher. The authors proposed approach to assessing the damage caused to land resources that were damaged by military actions on the regional territories and for territorial communities. Furthermore, it has been observed that for carrying out restoration works to eliminate the consequences of armed aggression and combat actions in the respective territories of Ukraine, there remains an important task of scientifically substantiated development and adoption of relevant regulatory and methodological documents. It is proposed to determine pilot projects and foreign grants for their development.